2020
DOI: 10.1029/2020wr027768
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Soil Erosion With Evolving Rills on Hillslopes

Abstract: Whereas current erosion models are successful in quantitative estimates of soil erosion by water flow, modeling the coevolution of geomorphological features, particularly rill network properties and soil erosion on hillslopes, is still a major challenge. In this study, we propose a rill evolution modeling approach and combine it with a rainfall-runoff and soil erosion model to simulate the feedback loop of hillslope geomorphic development and soil erosion processes. Rill evolution is mainly characterized by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Model simulation is an important approach to improve insight into the mechanism behind the soil erosion process. Many models have satisfactorily predicted soil erosion processes at different spatial and temporal scales, such as WEPP (Wu & Chen, 2020), USLE (Alewell et al, 2019), RUSLE (Mondal et al, 2017), and SWAT (Nearing et al, 2005). However, these models also have some drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Model simulation is an important approach to improve insight into the mechanism behind the soil erosion process. Many models have satisfactorily predicted soil erosion processes at different spatial and temporal scales, such as WEPP (Wu & Chen, 2020), USLE (Alewell et al, 2019), RUSLE (Mondal et al, 2017), and SWAT (Nearing et al, 2005). However, these models also have some drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The angle of the rill flow direction and the slope direction may differ due to the microtopography during the initial stages of rill development. This may also cause a difference between a modelled rill and a measured rill, although this is less pronounced for the later stages of rill network development [58,59]. It has also been shown that DTM in fine resolution can predict rill development well [60].…”
Section: Field-scale Rill Flow Validation-a Case Studymentioning
confidence: 99%
“…Also, Helming et al (1999) found that the small-scale drainage network of eroded slope runoff had similar characteristics to the river system when Horton's law and fractal Feature methods were utilized (Fang et al, 2018). Wu and Chen. (2020) believed that if the similarities exist, the knowledge that has been obtained at the river scale can be used to understand and simulate the rill network process.…”
Section: Introductionmentioning
confidence: 99%